Por une releture du Marco Polo de Paul Vidal de La Blache - Mercier, Guy (Finisterra, 1998)
RE-READING PAUL VIDAL DE LA BLACHE'S MARCO POLO - Although Paul Vidal de La Blache's work has been widely commented upon, his first works are barely known. This is the case, for instance, of his first book, "Marco Polo. Son temps et ses voyages", published in 1880. My purpose is to analyse the geographical content of that book and to elaborate a hypothesis as to its role in the institutionalisation of Vidalian thought.